(untitled) (Decentering European studies: perspectives on Europe from its beyond, 2025)
The ways in which the European Union interacts with its member states and the countries outside the bloc as a supranational political power can be analyzed at different levels: internal, regional, and global. In this book that aims to decentralize knowledge production about Europe, this section assembles works by Global South/Global East authors to incorporate perspectives and expertise from outside the EU. The three chapters that follow add value by presenting diverse external perceptions of Union politics and functioning and by casting new light on issues the EU has had to face recently.